Agricultural information and knowledge sharing: promising opportunities for agricultural information specialists - Ballantyne, Peter G. (2010)
The recent food crisis has pushed agriculture and food security back on to national and development agenda’s. Additional international funds have been mobilized, national and regional initiatives have been strengthened, and a wide range of new and innovative instruments and approaches have been promised. Most of these efforts call for greater investment in knowledge creation, information access, and the wider use of information and communication technologies (ICTs). This paper explores what this renewed interest might mean for information and communication specialists working in agriculture. Starting from an ‘innovation systems’ perspective, it highlights some promising opportunities for information and communication specialists. These include: working with farmer knowledge, using information and communication technologies (ICTs) to enable agricultural development activities, ensuring that public investments result in public goods whose benefits can travel, making agricultural content open and accessible, using the power of the ‘social’ web, and transforming the roles of library and information centers.